THE ROLE OF WOMEN'S SAVINGS AND LOANS PROGRAM IN INCREASING MEMBERS' INCOME FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Devita Lingga Pratiwi; Zuwardi Zuwardi (ADISAM PUBLISHER, 2023)
This study's goal is to comprehend how Simpan Pinjam Perempuan program works to increase employee pay from Islam's econ of qualitative research being done at the moment is deskriptively written research methodology. The information that was used was data primer, which used as a pr piece of information in the study by way of a conversation with lone remain Saving and Loans organization, and data second as the study's supporting information from websites and related documents. The study's findings demonstrate that the presence of the Women's Savings and Loans Program is very helpful to the community in meeting their needs, This is evident from the increasingly rapid business development, as well as the increasing income levels of members, besides that it also provides job opportunities for the surrounding community who do not have jobs. Women's Savings and Loans Program has already begun operating in accordance with the objectives and benefits specified, such as